2015
DOI: 10.3390/polym7091474
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, Mechanical and UV-Shielding Properties of Poly(Methyl Methacrylate)/Cerium Dioxide Hybrid Systems Obtained by Melt Compounding

Abstract: Thick and homogeneous hybrid film systems based on poly(methyl methacrylate) (PMMA) and CeO2 nanoparticles were synthesized using the melt compounding method to improve thermal stability, mechanical and UV-shielding properties, as well as to propose them for use in the multifunctional materials industry. The effect of the inorganic phase on these properties was assessed by using two different weight percentages of synthesized CeO2 nanoparticles (0.5 and 1.0 wt %) with the sol–gel method and thermal treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…The main absorption peaks for pure PMMA and GNPs/ PMMA nanocomposite are visible at 2992 cm −1 (O CH 3 , C H stretching), 2948 cm −l (C CH 3 , C H stretching), 1729 cm −l (C O stretching), 1434 cm −1 (O CH 3 bending), 1382 cm −1 (C CH 3 bending), 1238 cm −1 (C C O stretching), 1189 cm −1 (C O C bending), 1145 cm −1 (CH 2 bending) and 753 cm −1 (C O bending). [25][26][27] There is not much research available concerning the effect of bonding interaction between the PMMA and GNPs on the FTIR spectrum of the composite. The PMMA/GNPs nanocomposites fabricated here presented similar absorption peaks as a result of the variations in the bonding interaction between PMMA and GNPs at different concentrations of the GNPs.…”
Section: Resultsmentioning
confidence: 99%
“…The main absorption peaks for pure PMMA and GNPs/ PMMA nanocomposite are visible at 2992 cm −1 (O CH 3 , C H stretching), 2948 cm −l (C CH 3 , C H stretching), 1729 cm −l (C O stretching), 1434 cm −1 (O CH 3 bending), 1382 cm −1 (C CH 3 bending), 1238 cm −1 (C C O stretching), 1189 cm −1 (C O C bending), 1145 cm −1 (CH 2 bending) and 753 cm −1 (C O bending). [25][26][27] There is not much research available concerning the effect of bonding interaction between the PMMA and GNPs on the FTIR spectrum of the composite. The PMMA/GNPs nanocomposites fabricated here presented similar absorption peaks as a result of the variations in the bonding interaction between PMMA and GNPs at different concentrations of the GNPs.…”
Section: Resultsmentioning
confidence: 99%
“…With addition of CoNPs with and without DBSA, in the PMMA matrix, the absorption is increased showing incorporation of CoNPs in the structure of PMMA. This increase in the absorption intensity was more pronounced in the case when DBSA was added as an additive which clearly indicated that DBSA helped in better incorporation of CoNPs [4,19,21]. It can be noted that shift in the position of maximum absorption is not significant.…”
Section: Uv-vis Spectroscopymentioning
confidence: 83%
“…Poly(methyl methacrylate) (PMMA) is widely used in various fields such as optical sensors, light conduction, optical windows, or in biomedical, biomaterials, polymer electrolytes, molecular separations. [1][2][3][4] Nowadays, PMMA has been also used as the base to produce acrylic bone cements for artificial joint replacement, filling of bone defects, kyphoplasty, vertebroplasty. [5][6][7][8][9][10][11] Commercial bone cement is composed of two separated powder and liquid components.…”
Section: Introductionmentioning
confidence: 99%